2015
DOI: 10.1589/jpts.27.1481
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of neuromuscular joint facilitation (NJF) treatment on the standing balance in younger persons

Abstract: [Purpose] The aim of this study was to investigate the change in standing balance of younger persons after neuromuscular joint facilitation (NJF) treatment. [Subjects] The subjects were 57 healthy young people, who were divided into three groups: The NJF group, and the Proprioceptive Neuromuscular Facilitation (PNF) group and the control group. [Methods] Functional reach test and body sway were measured before and after intervention in three groups. Four hip patterns of NJF or PNF were used. Two-way ANOVA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The results imply that NJF progressive resistance exercise increases muscle strength, balance, and proprioception in junior soccer players. The former research studies suggested immediate effects of NJF intervention on knee muscle force and standing balance 6 , 7 ) . Dynamic balance of the lower limbs, especially on the unilateral side, is essential in sports training to improve sensorimotor performance and postural control and perhaps to reduce the risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The results imply that NJF progressive resistance exercise increases muscle strength, balance, and proprioception in junior soccer players. The former research studies suggested immediate effects of NJF intervention on knee muscle force and standing balance 6 , 7 ) . Dynamic balance of the lower limbs, especially on the unilateral side, is essential in sports training to improve sensorimotor performance and postural control and perhaps to reduce the risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed therapeutic mobilization techniques that had not been tested specifically in DDH but had shown positive results to improve joint stability in other pathologies. The protocol was based on proprioceptive neuromuscular facilitation (PNF) [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic mobilization techniques have not been tested specifically in DDH but have been shown to improve joint stability. Proprioceptive neuromuscular facilitation (PNF) improved joint stabilization in young adults [ 26 ]. PNF employs joint approximation to stimulate joint receptors, facilitate alpha motor neurons, and promote reflex muscle contraction in order to improve joint stability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that performing NJF in the knee joint can strengthen the muscle and shorten the integrated electromyography amplitude reaction time in healthy adults 5,6) . In addition, NJF in the hip joints can improve the standing balance function in healthy young people 7) .…”
Section: Introductionmentioning
confidence: 99%